2021
DOI: 10.1684/epd.2021.1342
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of perampanel in Chinese paediatric patients (2‐14 years) with refractory epilepsy: a retrospective, observational study

Abstract: Objective. We report our clinical experience of the effectiveness and tolerability of adjunctive perampanel treatment in a Chinese paediatric population with refractory epilepsy. We also compare the effectiveness and tolerability of perampanel with or without concomitant oxcarbazepine or levetiracetam. Methods. This retrospective observational study was conducted from September 2019 to September 2020 in the paediatric neurology clinics of two tertiary hospitals in the Chinese mainland. We reviewed the data obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…In pediatric epilepsy, previous studies found that adjunctive PER therapy appeared effective and tolerable 3–5 . A good efficacy was also seen in PER monotherapy, evidenced by a multicenter, retrospective, observational study 6 .…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In pediatric epilepsy, previous studies found that adjunctive PER therapy appeared effective and tolerable 3–5 . A good efficacy was also seen in PER monotherapy, evidenced by a multicenter, retrospective, observational study 6 .…”
Section: Introductionmentioning
confidence: 84%
“…2 In pediatric epilepsy, previous studies found that adjunctive PER therapy appeared effective and tolerable. [3][4][5] A good efficacy was also seen in PER monotherapy, evidenced by a multicenter, retrospective, observational study. 6 However, daily clinical experiences have shown large interindividual variability in the relationship between plasma PER levels and its clinical effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, the recent approval of perampanel means that few real-life studies on using perampanel in Chinese patients have been reported. Only Qu et al 11 found that perampanel was safe, tolerated, and effective in treating pediatric patients with refractory epilepsy aged 2-14 years in China, with a 50% responder and seizure freedom rate of 51.2% and 27.4%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data on the safety and efficacy of perampanel in the clinical setting involving Chinese pediatric patients are limited, [11][12][13] as perampanel has only recently been approved for use in China. Qu et al 11 found that perampanel, with or without concomitant oxcarbazepine or levetiracetam, is safe, well tolerated, and efficacious in pediatric patients aged 2-14 years with refractory epilepsy in a clinical setting. Liao et al 12 found that adjunctive perampanel (up to 12 mg/d) may be a suitable treatment for Chinese patients (aged ≥12 years) with focal seizures, with or without focal to bilateral tonic-clonic seizures, or generalized tonic-clonic seizures, with similar efficacy and safety or tolerability compared with non-Chinese patients.…”
mentioning
confidence: 99%
“…However, plasma concentrations of PER were not measured in the study, and the author concerned that they could not precisely assess the influence of concomitant enzyme inducers on the plasma levels of PER associated with seizure control and AEs [41]. Another retrospective observational study has suggested the effectiveness and safety of PER in Chinese pediatric patients (2-14 years) with refractory epilepsy [42]. But the author did investigate the plasma concentration of PER in these children, too.…”
Section: Plasma Concentrationsmentioning
confidence: 99%